2012
DOI: 10.1590/s1981-67232012005000040
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades de pasta de amidos de arroz nativo e acetilados

Abstract: O amido de arroz apresenta características favoráveis a muitas aplicações industriais; no entanto, a natureza hidrofílica do amido na forma nativa pode apresentar algumas limitações para determinados tipos de processamento. Neste estudo, amido de arroz com médio teor de amilose foi acetilado sob catálise alcalina em duas condições reacionais para produzir acetatos de amido com diferentes graus de substituição (GS). A introdução de grupos acetila ao amido foi confirmada por espectroscopia de infravermelho com t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…As the glycerol bands did not show differences in the spectra, so only a concentration of starch was selected, the film with better mechanical properties. S, S 0.6 and S 1.1 starch granules and S25, S 0.6 25 and S 1.1 25 films infrared spectra between 400 cm -1 and 4000 cm -1 were recorded using a FTOR spectrophotometer (FTLA 2000, ABB, Zurich) ( Bartz et al, 2012). Tablets were prepared by mixing the starch samples with KBr with a ratio of 1:100 (sample weight: KBr weight).…”
Section: Fourier Transformed Ir Spectroscopy (Ftir)mentioning
confidence: 99%
See 3 more Smart Citations
“…As the glycerol bands did not show differences in the spectra, so only a concentration of starch was selected, the film with better mechanical properties. S, S 0.6 and S 1.1 starch granules and S25, S 0.6 25 and S 1.1 25 films infrared spectra between 400 cm -1 and 4000 cm -1 were recorded using a FTOR spectrophotometer (FTLA 2000, ABB, Zurich) ( Bartz et al, 2012). Tablets were prepared by mixing the starch samples with KBr with a ratio of 1:100 (sample weight: KBr weight).…”
Section: Fourier Transformed Ir Spectroscopy (Ftir)mentioning
confidence: 99%
“…Several authors have reported the use of chemically modified starches to obtain new materials, e.g. pre gelatinized, acid modified and acetylated starches (Golachowski et al, 2015;Mbougueng et al, 2012;Bartz et al, 2012). On particular, acetylated starch is a starch ester that has been widely studied over the last two decades (Chi et al, 2008).…”
Section: Introdutionmentioning
confidence: 99%
See 2 more Smart Citations
“…estão relacionadas ao alongamento C-O e C-C. 24,26 Na Figura 5 observa-se o espectro de infravermelho do trimetafosfato de sódio puro. As bandas entre 517 a 687 cm -1 são relacionadas ao estiramento vibracional das ligações, O-P-O e/ou (P=O); as bandas em 756 a 776 cm -1 , são atribuídas ao estiramento simétrico (P-O-P); as bandas na região de 880 a 1022 cm -1 relacionam-se ao estiramento vibracional assimétrico (P-O-P).…”
Section: Caracterizaçõesunclassified